The simulation design in health and nursing: A scoping review - George Oliveira Silva; Luciana Mara Monti Fonseca; Karina Machado Siqueira; Fernanda dos Santos Nogueira deGóes; Laiane Medeiros Ribeiro; Natália Del' Angelo Aredes (Wiley, 2023)
Abstract Aims The aims of this study were to map the components of the simulation design in health and nursing and to propose a classification based on their definitions to support the planning of simulation‐based experiences. Design Scoping review. Method Searches were performed in the databases LILACS, Embase, MEDLINE/PubMed, SCOPUS, Web of Science, Google Scholar and ProQuest Thesis and Dissertation were performed, without time limitation, to identify studies about simulation design. Results This study mapped 19 components of the simulation design found in 26 studies included, which can contribute to the development of simulation‐based experiences, classified into structural, methodological and theoretical-pedagogical components. The simulation design can be described according to its fundamental components: structural-define the basic formulation of a simulation in terms of infrastructure and conceptual framework; methodological-define the participants, roles and the instruction format; and theoretical-pedagogical-define the educational references used to support the simulation strategy.